Retrospektívna analýza krátkodobých a strednodobých výsledkov perkutánnej endovaskulárnej liečby pacientov s aneuryzmou abdominálnej aorty - Tóth, M; Maďarič, J; Balázs, T; Mikuláš, J; Hladíková, D; Bažík, R; Drangová, E; Urlandová, T; Klepanec, A; Vulev, I (Rozhledy v chirurgii, 2013)
INTRODUCTION: Endovascular abdominal aortic aneurysm repair (EVAR) is a modern and, compared to conventional open surgery, less invasive therapeutic strategy with short-term lower morbidity and mortality. The aim of our retrospective analysis was the assessment of safety, technical success, short-term and mid-term results of elective patients scheduled for total percutaneous EVAR implantation (PEVAR). MATERIAL AND METHODS: One hundred and sixteen consecutive patients (M:F 104:12, age 71±9 years, maximum AAA diameter 60±14mm) underwent elective PEVAR between January 2009 and August 2012. All the patients were treated under local anaesthesia by total percutaneous approach via femoral access. The immediate technical success of stentgraft implantation as well as the presence of 30-day and 1-year complications and the need of reintervention rate were assessed. RESULTS: In 115/116 patients (99.1%),immediate technical success of the procedure was recorded, with no need of conversion to open surgery; in 1 patient (0.9%) the performance technically failed due to unfavourable arterial anatomy. The mortality in 30-day follow-up was 2.6% (3 patients), during 1-year follow-up it amounted to 8.6% (10 patients), without causal relationship with stentgraft implantation. Overall event-free survival was 85% (98/116) without serious complications (mortality, MI, stroke, reintervention, severe ischemic complication) in the one-year follow-up period. CONCLUSION: Endovascular AAA repair is a safe and feasible method with low mortality and acceptable complication rate in patients scheduled for EVAR implantation. Percutaneous approach allows for the extension of indications also for the highest-risk group of polymorbid patients. Technical feasibility and adequate periprocedural management are essential for further reduction in adverse events after PEVAR.
Keywords: Survival Analysis; Retrospective Studies; pooperační komplikace; Humans; mužské pohlaví; Middle Aged; Treatment Outcome; Postoperative Complications; endovaskulární výkony; Aortic Aneurysm, Abdominal; Stents; senioři; Female; výsledek terapie; analýza přežití; stenty; Male; retrospektivní studie; lidé středního věku; Endovascular Procedures; aneurysma břišní aorty; ženské pohlaví; abdominal aortic aneurysm - endovascular treatment - stentgraft - percutaneous approach.; lidé; Aged